ANALYSIS OF WRITING MATERIALS AND ACTIVITIES IN “ WHEN ENGLISH RINGS A BELL” IN TEXTBOOK - Pasaribu, Rutli Nuriza; Tamba, Evi Endang; Saragih, Erikson (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Abstract. A Textbook is a reference for teachers and students on learning. (Awasthi, 2006) Says textbooks are learning material for both teachers and students in the learning and teaching process, especially in students for learning activities. This study aims to analyze the material and student activity in textbooks. The analysis is focused on the presentation of the materials and assignments written by the students. This research is descriptive qualitative using content analysis. From the aspect of presenting writing material and activities, all writing materials and assignments are in the form of a guide. writing, because students are asked to write responses, in limited length, to the instructions given. This study shows that writing assignments in textbooks are proportionately covered. The findings suggest that independent references to vocabulary and grammar are required for independent study. With written assignment activities presented in the textbook material, students understand better the previous lesson and are more active in the learning process. The topics presented are diverse so that students have the opportunity to explain the topic in different ways.